Development of high-performance polydimethylsiloxane-based nanofibrous composite membranes for phenol removal from wastewater - Jin, Meng-Yi (2018)
Treatment of organic-containing wastewater has drawn increasing attention in recent years. Among the major pollutants, phenol has become a rising concern due to its high toxicity and carcinogenicity. On the other hand, phenol is recognized as a valuable chemical for industrial application such as production of phenolic resins. Hence, research and development of treatment processes for effective removal and recovery of phenol from wastewater before discharge is of high interest. Among all the existing technologies, membrane process, particularly, the membrane-based aqueous-aqueous extractive process, has been evidenced to be a promising technology ascribed to its appealing features including independent operation of the receiving solutions, point-source treatment of industrial effluents and low energy consumption. However, one of the main challenges that impedes the application of the aqueous-aqueous extractive processes is the shortage of specially designed membranes capable of extracting the organic compounds into the receiving medium with high efficiency and excellent stability. This study aims to develop high-performance nanofibrous composite membranes for phenol removal in the aqueous-aqueous extractive processes. Three generations of polydimethylsiloxane/polyvinylidene fluoride (PDMS/PVDF) nanofibrous composite membranes have been developed with focus on fabrication of highly porous tiered electrospun nanofibrous membranes (ENMs) as the supportive layers, optimization of the PDMS macromolecular architectures through different cross-linking pathways, and incorporation of ZIF-8 as transport fillers in the PDMS matrix, respectively. The developed nanofibrous composite membranes exhibited progressive enhancement in k0 (overall mass transfer coefficient, OMTC) values from 4.1 ± 0.3 x 10-7 m/s in the 1st-generation membrane, 18.3 ± 1.3 x 10-7 m/s in the 2nd-generation membrane, to 35.7 ± 1.1 x 10-7 m/s in the 3rd-generation membrane for phenol removal from wastewater. In addition, the effects of PDMS coating solution preparation, pre-wetting agent for substrate, PDMS precursor molecular weight, cross-linker amount, ZIF-8 addition protocol, and ZIF-8 loading on the phenol removal efficiency were studied systematically. In conclusion, this thesis presents a detailed study on the design and development of high-performance nanofibrous composite membranes for phenol removal in the aqueous-aqueous extractive processes. The findings obtained from this study provide insights and guidelines for fabricating highly efficient membrane materials for organic removal and recovery in various membrane extractive processes.